The Effect of Human Resources Competencies and Work Environment on Employee Performance with Work Motivation as an Intervening Variable at J&T Express Makassar - Pratama, Putra Agung; Nurmiati; Wahyudi; Jafar, Akhmad; Sofyan, A. Syathir (Best Journal of Administration and Management, 2025)
This study aims to determine the effect of HR competency and the work environment on employee performance, with work motivation as an intervening variable at J&T Express Makassar. This is an associative study with a quantitative approach. The population in this study were employees working at J&T Express Makassar. This study used a saturated sampling technique due to the small population size; therefore, the sample in this study used the entire population as respondents, totaling 130 people. The study used primary data through a questionnaire. The results indicate that HR competency and the work environment have a positive and significant influence on employee performance. Furthermore, work motivation has been shown to act as an intervening variable, strengthening the relationship between HR competency and the work environment on employee performance.